Factors influencing sedentary behaviours after stroke: findings from qualitative observations and interviews with stroke survivors and their caregivers - Jennifer Hall; Sarah Morton; Claire F. Fitzsimons; Jessica Faye Hall; Rekesh Corepal; Coralie English; Anne Forster; Rebecca Lawton; Anita Patel; Gillian Mead; David J. Clarke (BMC, 2020)
Abstract Background Stroke survivors are more sedentary than healthy, age-matched controls, independent of functional capacity. Interventions are needed to encourage a reduction in overall sedentary time, and regular breaks in prolonged periods of sedentary behaviour. This study captured the views and experiences of stroke survivors and their caregivers related to sedentary behaviour after stroke, to inform the development of an intervention to reduce sedentary behaviour. Methods Mixed-methods qualitative study. Non-participant observations were completed in two stroke services, inclusive of inpatient and community settings in the United Kingdom. Semi-structured interviews were conducted with stroke survivors and their caregivers (if available) at six- or nine-months post-stroke. Underpinned by the capability, opportunity and motivation (COM-B) model of behaviour change, observational data (132 h) were analysed thematically and interview data (n = 31 stroke survivors, n = 12 caregivers) were analysed using the Framework approach. Results Observation participants differed in functional ability whereas stroke survivor interviewees were all ambulant. Six themes related to sedentary behaviour after stroke were generated: (1) sedentary behaviour levels and patterns after stroke; (2) the physical and social environment in the stroke service and in the home; (3) standing and movement capability after stroke; (4) emotion and motivation after stroke; (5) caregivers' influence on, and role in influencing stroke survivors' sedentary behaviour; and (6) intervening to reduce sedentary behaviour after stroke. Capability, opportunity and motivation were influenced by the impact of the stroke and caregivers' inclination to support sedentary behaviour reduction. Stroke survivors reported being more sedentary than they were pre-stroke due to impaired balance and co-ordination, increased fatigue, and reduced confidence in mobilising. Caregivers inclination to support stroke survivors to reduce sedentary behaviour depended on factors including their willingness to withdraw from the caregiver role, and their perception of whether the stroke survivor would act on their encouragement. Conclusions Many stroke survivors indicate being open to reducing sedentary behaviour, with appropriate support from stroke service staff and caregivers. The findings from this study have contributed to an intervention development process using the Behaviour Change Wheel (BCW) approach to develop strategies to reduce sedentary behaviour after stroke.